"What pressure ulcers mean to me?" Representations of pressure ulcer in persons with spinal cord injury: A qualitative study. Issue 4 (November 2020) - GOURLAN, Mathieu; PELLECHIA, Alessandra; ROBINEAU, Sandrine; FOULON, Bernard; GAULT, Dominique; LEFORT, Marc; GOOSSENS, David; MATHIEU, Sarah; LAFFONT, Isabelle; DUPEYRON, Arnaud; NINOT, Gregory; GELIS, Anthony
Abstract: Objectives: Explore the perceptions and beliefs related to pressure ulcers (PU), their prevention and treatment strategies, in order to discuss potential learning objectives for PU-related therapeutic education in persons with spinal cord injury (SCI). Design: Qualitative study, using grounded theory for the analysis of data collected via a questionnaire. Setting: Nine SCI referral centers, inpatient care. Participants: 131 persons with SCI were included. 76% were male, and 65% presented with paraplegia. The median age was 48 years (33.5; 58) and median time since injury was 11 years (3; 24.5). 70% had experience with PU. Interventions: None. Main outcome measures: Data collection via an open-ended questionnaire on the representation of PU, its prevention and life experience of having a PU. Results: Six categories were identified: (1) identifying what might become problematic, (2) daily preventive actions, (3) detecting the early signs, (4) managing the early signs, (5) need for care, (6) experience with PU and being bedridden. Pressure ulcers have dramatic consequences on psychosocial health. Prevention and treatment require self-management skills, such as self-risk assessment abilities, self-detection skills and problem-solving strategies, to optimise daily PU prevention in persons with SCI. Conclusion: PU prevention tackled by persons with SCI bears some specificities that the physician must take into account in the construction of a self-management program in this high-risk population. Highlights: Persons with SCI develop their own perception of PU risk and their own strategy to self-manage the early signs of PU. In self-management programs, it is important to focus on how a person with SCI perceives his own likelihood to develop a PU. Patients should be accompanied to create a personalized strategy to self-screen for beginning PUs. Self-management interventions should promote problem-solving strategies to face with early stages of PU.